Pengaruh Kualiatas Makanan Dan Suasana Terhadap Kepuasan Konsumen Pada Pizza House Di Kota Lhokseumawe - Intan Syafriani; H Heriyana; Yusniar Yusniar (Department of Management Faculty of Economics and Business, UNIVERSITAS MALIKUSSALEH, 2022)
This study examined the effect of food quality and atmosphere on consumer satisfaction at Pizza House in Lhokseumawe City. This study used primary data obtained by distributing questionnaires to 115 respondents who were selected using a non-probability sampling method with purposive sampling technique. The data analysis method used was multiple linear regression with the help of SPSS 24.0. The results partially indicated that food quality significantly influenced consumer satisfaction at Pizza House in Lhokseumawe City, and atmosphere significantly influenced consumer satisfaction at Pizza House in Lhokseumawe City. Simultaneously, food quality and atmosphere significantly influenced consumer satisfaction at Pizza House in Lhokseumawe City.